Maria Pelaez at 135 m of Her Winning 200 m Race at the 1998 Goodwill Games in New York (Misty Hyman is in the Next Lane) - Rushall, B. S. (1999)
Video pictures (13 frames) and the appropriate technical/ biomechanical explanations for Maria Pelaez at 135 m of Her Winning 200 m Race at the 1998 Goodwill Games in New York (Misty Hyman is in the Next Lane).